The Effect of Early Childhood Sexual Abuse on Mental Health Among Postpartum Women Visiting Public Health Facilities in Bahir Dar City, Ethiopia: Multicenter Study - Belete H; Misgan E; Mihret MS (Dove Medical Press, 2020)
Habte Belete,1 Eyaya Misgan,2 Muhabaw Shumye Mihret3 1Psychiatry Department, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Gynecology and Obstetrics Department, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 3Department of Clinical Midwifery, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Muhabaw Shumye MihretDepartment of Clinical Midwifery, College of Medicine and Health Sciences, University of Gondar, PO. Box 196, Gondar, EthiopiaTel +251 918473798Fax +251 581110004 Email muhabawshumye@gmail.comBackground: There is a scarcity of evidence regarding the effects of early childhood sexual abuse on mental health among women in Sub-Saharan Africa. The purpose of this study was to assess the proportion of postpartum depression and associated factors among postnatal women in care in public health facilities of Bahir Dar city, northwest Ethiopia. This study also aimed at evaluating the effect of early childhood sexual abuse on postpartum depression.Methods: A multicenter cross-sectional study was conducted among 988 postpartum women in care at Bahir Dar city’s public health facilities. A two-stage sampling technique and interviewer administered structured questionnaire were utilized. Edinburgh Postnatal Depression Scale (EPDS) with a cutoff point of ≥ 12 was employed to report postpartum depression. Binary logistic regression model was fitted and the level of significance was reported based on AOR with 95% CI at p-value of < 0.05.Results: The prevalence of postpartum depression was 33.8% (95% CI: 31, 37) and 55.3% (95% CI: 46, 64) among all study participants and mothers having a history of childhood sexual abuse, respectively. Participants’ age of < 25 years (AOR = 3.1; 95% CI: 1.9, 5.3) and 25– 34 years (AOR= 2.0; 95% CI: 1.3, 3.2), family size of > 5 (AOR = 2.5; 95% CI: 1.1, 5.7), alcohol use (AOR = 2.2; 95% CI: 1.6, 2.9), history of childhood sexual abuse (AOR = 2.8; 95% CI: 1.9, 4.3), joblessness (AOR = 1.4; 95% CI: 1.1, 1.9) and growing up with biological mothers (AOR = 0.5; 95% CI: 0.4, 0.8) have stastical significant association with postpartum depression as compared to the respective reference group.Conclusion: A significantly higher burden of postpartum depression was observed among mothers with a history of childhood sexual abuse. Thus, controlling childhood sexual abuse and other psychosocial determinants would improve maternal mental wellness.Keywords: Bahir Dar city, childhood sexual abuse, Ethiopia, postpartum depression